2012
DOI: 10.2169/internalmedicine.51.8215
|View full text |Cite
|
Sign up to set email alerts
|

Central Neurogenic Hyperventilation in Anti-NMDA Receptor Encephalitis

Abstract: Central neurogenic hyperventilation (CNH) is a rare condition that is generally associated with infiltrative tumors of the brainstem. Respiratory dysfunction, particularly central hypoventilation, is common in anti-Nmethyl D-aspartate (NMDA) receptor encephalitis. CNH, to the best of our knowledge, has not been described previously in this disease. A 24-year-old woman was diagnosed with anti-NMDA receptor encephalitis secondary to ovarian teratoma. In addition to the typical symptoms of the disease, recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Central hypoventilation is a significant clinical feature of anti-NMDAR encephalitis. However, similarly to a report from Vural et al [ 32 ], the patient in the second case suffered from hyperventilation, which was possibly central neurogenic hyperventilation. The inactivation of GABAergic neurons due to an antibody-mediated decrease in NMDA receptors may be involved in the complexity of some abnormal movements via disinhibition of a brainstem central pattern generator [ 33 ], which is the possible underline mechanism of central neurogenic hyperventilation.…”
Section: Discussionsupporting
confidence: 79%
“…Central hypoventilation is a significant clinical feature of anti-NMDAR encephalitis. However, similarly to a report from Vural et al [ 32 ], the patient in the second case suffered from hyperventilation, which was possibly central neurogenic hyperventilation. The inactivation of GABAergic neurons due to an antibody-mediated decrease in NMDA receptors may be involved in the complexity of some abnormal movements via disinhibition of a brainstem central pattern generator [ 33 ], which is the possible underline mechanism of central neurogenic hyperventilation.…”
Section: Discussionsupporting
confidence: 79%
“…A previous study indicated that orofacial-lingual dyskinesia, tremor, and dystonia were the common types of involuntary movements in anti-NMDAR encephalitis 13. Histological data have revealed the distribution of NMDAR in the brainstem, but the cause of central hypoventilation in patients with anti-NMDAR encephalitis remains unclear—it may be associated with secondary brainstem lesions or a functional neurotransmitter imbalance 1415. Severe patients exhibiting decreased consciousness and central hypoventilation generally require artificial-airway- and ventilator-assisted breathing, while involuntary movements of the face and dystonia may have a considerable impact on airway management 12…”
Section: Discussionmentioning
confidence: 99%
“…In addition to those characteristic manifestations, central neurogenic hyperventilation has been reported in such patients [60]. The cranial nerves are also involved in anti-NMDAR encephalitis.…”
Section: Clinical Manifestationsmentioning
confidence: 99%